2000
DOI: 10.1002/1529-0131(200003)43:3<656::aid-anr23>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of the antiinflammatory effects of methotrexate by the nonselective adenosine receptor antagonists theophylline and caffeine: Evidence that the antiinflammatory effects of methotrexate are mediated via multiple adenosine receptors in rat adjuvant arthritis

Abstract: Objective. Weekly low-dose methotrexate (MTX) remains the mainstay of second-line therapy for rheu-matoid arthritis (RA). We have previously reported that adenosine, acting at specific receptors on inflammatory cells, mediates the antiinflammatory effects of MTX in both in vitro and in vivo models of acute inflammation, but the mechanism by which MTX suppresses the chronic inflammation of arthritis remains controversial. The present study was undertaken to further investigate the means by which adenosine media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
104
1
3

Year Published

2001
2001
2012
2012

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 168 publications
(113 citation statements)
references
References 47 publications
4
104
1
3
Order By: Relevance
“…It is also interesting to note that it is likely that the inhibitory effects of methotrexate on osteoclast-mediated bone destruction are mediated by the higher levels of adenosine released by methotrexate-treated cells and tissues which interact with A 2A and A 3 receptors [53]. Indeed, in the adjuvant arthritis model studied by Teramachi and colleagues, the adenosine receptor antagonists theophylline and caffeine reverse the anti-inflammatory effects of methotrexate [54].…”
Section: Discussionmentioning
confidence: 99%
“…It is also interesting to note that it is likely that the inhibitory effects of methotrexate on osteoclast-mediated bone destruction are mediated by the higher levels of adenosine released by methotrexate-treated cells and tissues which interact with A 2A and A 3 receptors [53]. Indeed, in the adjuvant arthritis model studied by Teramachi and colleagues, the adenosine receptor antagonists theophylline and caffeine reverse the anti-inflammatory effects of methotrexate [54].…”
Section: Discussionmentioning
confidence: 99%
“…Their findings showed a possible involvement of A 1 AR in normal osteoclastogenesis. Montesinos et al 28,29 has reported that adenosine acts as the suppressive factor in inflammation. In their model, MTX administration induced a significant level of adenosine; however, its level is o170 nM, which concentration are able to activate only the high-affinity receptors.…”
Section: Discussionmentioning
confidence: 99%
“…27 At the height of inflammation, the destruction of host tissue combined with damaged microcirculation and hypoxia leads to elevation of extracellular adenosine. 28 Animal models of asthma, 29 arthritis, 30 sepsis, 31 inflammatory bowel disease 32 and wound healing 33 have helped to elucidate the regulatory roles of adenosine in dictating the development and progression of disease. Adenosine potently inhibits a wide range of T-cell responses, including cell proliferation, 34 synthesis of IL-2 and proinflammatory cytokines, such as IFN-c and TNF-a, 35 and some of the earliest steps of T-cell activation, which were reported to be mediated mainly by the adenosine A 2A receptor.…”
Section: Pf Inhibits the Functions Of T Cells And Differentiation Of mentioning
confidence: 99%